Review & Proposal for a Cloud based Framework for Indian Higher Education (International Journal of Engineering and Computer Science, 2014)
we are moving towards a smart evolution a Social Learning era fostering hype towards cloud enhancement and an era of fast change. We are always on the lookout to find better ways to accomplish our ordeals. In spite of a harsh global economic situation, our ability to fashion new technologies, to harness the power of information appears healthier than ever. In this paper, we are going to focus more on reviewing the current pace of cloud invasion on higher education. This will also list out the best practice to be implemented in order to accomplish what we foresee as a smart era.